Sick happens: The effect of worker health shocks on coworkers' employment and health behavior - Wolfgang Frimmel; Rene Wiesinger (Johannes Kepler University of Linz, Department of Economics, 2024)
We analyze how a worker's severe health shock affects the employment and health behavior of their older coworkers. We link comprehensive administrative data on labor market histories and health records from Austria to identify coworker networks and severe health shocks in small firms, which cause substantial increases in healthcare expenditures, absenteeism, and mortality, as well as persistent reductions in the labor supply of affected workers. Combining a matching approach with a difference-in-difference framework, we find a significant impact of a health shock on the labor market outcomes and health behavior of older coworkers. Affected coworkers are about 2.3 percentage points more likely to be employed in the shock firm and tend to delay retirement. Although there is no change in daily earnings and earnings growth, coworkers are more likely to receive special bonus payments after leaving the firm. The employment effects are larger when the health shock affects a high-skilled worker and when the shocked worker leaves the firm after the health shock. Finally, we find that female coworkers in the treatment group are more likely to have a mammography, especially in response to health shocks due to cancer. We find no statistically significant effects on participation in general health check-ups and PSA tests, or on coworker absenteeism.
Keywords: I10; I12; J20; J21; 330; coworker health shock; employment; retirement; health behavior; difference-in-difference